Implementasi Jaringan Syaraf Tiruan (JST) untuk Mengenali Pola TandaTangan dengan Metode Backpropagation - Farras Ashar, Suthan; Iqbal, Farhan; Sofinah Harahap, Lailan (Journal of Multidisciplinary Inquiry in Science, Technology and Educational Research, 2025)
Artificial Neural Networks (ANN) is a computer technology in the field of artificial intelligence that is able to understand complex data patterns. One of ANN's technological capabilities is being able to predict solutions based on training patterns provided during the system learning process. This study aims to apply the signature pattern by applying ANN using the Backpropagation method. Backpropagation method is one of the learning algorithms related to the preparation of weights based on the value of errors in learning. The image will be processed using the Backpropagation method which will be obtained by the introduction. The results introduce 50 signature data samples and 50 signature sample data. The test is carried out using 50 samples, where each sample will be requested once. From the results of the research that has been done it can be concluded that the results obtained from the parameters with a learning rate of 0.5, epoch 100, objectives 1e-5 and momentum 0.9 with the results of 68% system testing.